Association of first trimester maternal vitamin D, ferritin and hemoglobin level with third trimester fetal biometry: result from cohort study on vitamin D status and its impact during pregnancy and childhood in Indonesia - Raden Tina Dewi Judistiani; Tita Husnitawati Madjid; Setyorini Irianti; Yessika Adelwin Natalia; Agnes Rengga Indrati; Mohammad Ghozali; Yunia Sribudiani; Tetty Yuniati; Rizky Abdulah; Budi Setiabudiawan (BMC, 2019)
Abstract Introduction The role of vitamin D in placental functions and fetal growth had been addressed in many reports with conflicting results. However, such report is limited for Indonesian population. The aim of this study was to explore the association between maternal vitamin D level in the first trimester and fetal biometry in the later stage of pregnancy with adjusted OR for other determinants like hemoglobin and ferritin level. Methods From July 2016 a prospective cohort study of pregnant women had begun in four cities in West Java, Indonesia. Data on maternal vitamin D, ferritin, hemoglobin level, maternal demography and fetal biometry were analyzed with linear regression. Results Among 203 recruited women, 195 (96.06%) had hypovitaminosis D. One hundred fifty two (75%) were in deficient state and 43 women (21%) were in insufficient state. Women with insufficient vitamin D had the highest proportion of anemia, while women with normal vitamin D level had the highest proportion of low ferritin level. Maternal serum vitamin D showed significant associations with biparietal diameter (β = 0.141, p = 0.042) and abdominal circumference (β = 0.819, p = 0.001) after adjustment with maternal age, pre-pregnancy body mass index, parity, serum ferritin level, and hemoglobin level. Conclusion Our study suggested that sufficient maternal vitamin D level was an important factor to improve fetal growth and development.